ON SCIENTIFIC AND MEDICAL PERSONNEL TRAINING AT V.I. SHUMAKOV FEDERAL RESEARCH CENTER OF TRANSPLANTOLOGY AND ARTIFICIAL ORGANS OF THE MINISTRY OF HEALTHCARE OF THE RUSSIAN FEDERATION (Вестник трансплантологии и искусственных органов)
.